Development of a MATLAB-Based CGPA and Final Exam Goal Calculator to Enhance Academic Planning in Higher Education - Ahmad Jamil, Nor Shafiqah; Mohamad Yunos, Nurhazirah; Mahat, Aishah; Khalid, Ahmad Khudzairi; Arifin, Nur Syamilah; Tukiman, Norbaiti (Journal of ICT in Education, 2025)
In higher education, the Cumulative Grade Point Average (CGPA) serves as a vital metric for assessing academic performance and shaping students’ future opportunities. However, many students struggle to plan their CGPA since they have trouble predicting their final examination marks to be achieved after getting the carry marks. Hence, this study addresses these challenges by developing an intuitive CGPA and final examination goal calculator using a graphical user interface (GUI) in MATLAB. A comprehensive flowchart for the development process is also provided, along with a brief explanation of the interface for both calculators to guide users. Additionally, demonstrations of the calculators are illustrated through examples. A user perception survey was conducted to evaluate the usability, user experience, and interface quality of both calculators. The findings suggest that these calculators have a positive impact on students' academic planning at two key stages: the beginning of the semester and the end, after receiving ongoing assessment marks.